KANDUNGAN MINERAL (Fe, Ca DAN P) KUKIS SUKUN DENGAN RASIO TEPUNG TEMPE DAN TEPUNGA UDANG REBON - Romdatul Sholeha; Netti Herawati; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The aim of this study was to obtain the best formula of breadfruit cookies formulation that meet quality standart of cookies (SNI 01-2973-1992) especially mineral contents. This research used a Completely Randomized Design (CRD) with four treathments and four replications. The treatments on this study wereKP 1(small shrimp flour 1%, tempeh flour 20%), KP2 (small shrimp flour 6%, tempeh flour 15%), KP3 (small shrimp flour 11%, tempeh flour 10%), and KP4(small shrimp flour 16%, tempeh flour 5%). The results were analyzed statistically by Analysis of Variance (Anova) and further tested with DNMRT at level of 5%. The results show that the treatments significantly different ash but not significantly in iron. The best treatment on this research was KP1 with ash 1,87% and iron 0,10%. There are 4 mg iron in one cookie. Key Words :Cookies, breadfruit, tempeh flour, small shrimp flour, mineral, iron